Ataxia telangiectasia mutated: The potential negative regulator in platelet-derived growth factor-BB promoted proliferation of pulmonary arterial smooth muscle cells - Qin, Chaoyi; Zan, Yiheng; Xie, Liang; Liu, Hanmin (Frontiers in Cardiovascular Medicine, 2022)
Objective To study the role of ataxia telangiectasia mutated (ATM) in the platelet-derived growth factor (PDGF)-BB-induced proliferation of pulmonary arterial smooth muscle cells (PASMCs) through reactive oxygen species (ROS) formation. Methods Primary cultures of PASMCs were treated with different concentrations of PDGF-BB or exogenous hydrogen peroxide (H2O2). The activation level of ATM and the proliferation level of PASMCs were measured by immunofluorescence staining and Cell Counting Kit-8, respectively. Moreover, NADPH oxidase 2 (NOX2) and intracellular H2O2 were detected under the stimulation of different levels of PDGF-BB by Western blot and dihydroethidium staining. Results Both the control group and 50 ng/ml of the PDGF-BB group showed significantly higher levels of phosphorylation ATM compared to other groups (P < 0.05). With the ATM inhibitor, 50 ng/ml of the PDGF-BB group showed further increased proliferative level compared to the 10 ng/ml (P < 0.05). Both the levels of NOX2 and H2O2 showed dose-dependent manners under PDGF-BB stimulation (P < 0.05). ATM could be activated by H2O2 upon a dose-dependent way, except for the 500 μM H2O2 group. Under 200 μM H2O2 stimulation, proliferation level decreased significantly (P < 0.05), while no significant difference was shown with the addition of ATM inhibitor (P > 0.05). Conclusion Our study first established ROS-induced ATM activation in PDGF-BB-stimulated proliferation of PASMCs. Inhibition of ATM had promoted effects on the proliferation of PASMCs under the excessive levels of PDGF-BB and H2O2. Our study might provide a novel promising target for the treatment of pulmonary arterial hypertension (PAH).